An integrated community and ecosystem-based approach to disaster risk reduction in mountain systems. Issue 94 (April 2019) - Klein, Julia A.; Tucker, Catherine M.; Steger, Cara E.; Nolin, Anne; Reid, Robin; Hopping, Kelly A.; Yeh, Emily T.; Pradhan, Meeta S.; Taber, Andrew; Molden, David; Ghate, Rucha; Choudhury, Dhrupad; et al.
Highlights: Over 70% of disaster-related deaths from 2005 to 2014 occurred in mountainous regions. Experiences in mountains reveal principles to guide disaster risk reduction (DRR). Effective DRR addresses both community and ecosystem health. DRR governance should fit local needs and requires local to global partnerships. Successful DRR actions focus on capacity building, inclusive knowledge, and equity. Abstract: The devastating 2015 earthquakes in Nepal highlighted the need for effective disaster risk reduction (DRR) in mountains, which are inherently subject to hazards and increasingly vulnerable to extreme events. As multiple UN policy frameworks stress, DRR is crucial to mitigate the mounting environmental and socioeconomic costs of disasters globally. However, specialized DRR guidelines are needed for biodiverse, multi-hazard regions like mountains. Ecosystem-based disaster risk reduction (Eco-DRR) emphasizes ecosystem conservation, restoration, and sustainable management as key elements for DRR. We propose that integrating the emerging field of Eco-DRR with community-based DRR (CB-DRR) will help address the increasing vulnerabilities of mountain people and ecosystems. Drawing on a global mountain synthesis, we present paradoxes that create challenges for DRR in mountains and examine these paradoxes through examples from the 2015 Nepal earthquakes. We propose four principles for integrated CB- and Eco-DRR that address these challenges: (1) governance and institutional arrangements that fit local needs; (2) empowerment and capacity-building to strengthen community resilience; (3) discovery and sharing of constructive practices that combine local and scientific knowledge; and (4) approaches focused on well-being and equity. We illustrate the reinforcing relationship between integrated CB- and Eco-DRR principles with examples from other mountain systems worldwide. Coordinated community and ecosystem-based actions offer a potential path to achieve DRR, climate adaptation, sustainable development, and biodiversity conservation for vulnerable ecosystems and communities worldwide.